Enhancing educational community space at Kampung Buku Langkawi through ecological approach - Zainal Abidin, Hazafizah (2018)
Community space is the phase area which is showing the various life among people (Karen E. and Trinidad R., 2014, p. 183). This study is to enhance a learning space for the community within social sustainability through an ecological approach at Kg Buku Langkawi, Kedah. Kg Buku Langkawi has the potential to enhance the community learning space for the user by using the existing flora and fauna to create the natural concept. The data were collected and analyzed to identify the issues and potential of the area. Then, the final of this study will come out with a new master plan development, which consists of design and approach to achieve the design goal. There needs some approach to implement this study. This study is for creating the strategies for enhancing the learning and community space with ecological and knowledge environment.